Ritualizirane transformacije digitalnih Pepeljuga: Postfeministička etika ljepote u videovodiču o šminkanju - Brigita Miloš ([sic])
The paper explores the relationship between Heather Widdows's theoretical proposition of beauty as an ethical ideal, or of beauty as a "moral matter" (Widdows 2) and the particular manifestation of doing beauty through the example of the video make-up tutorial named "Foundation Routine For Acne/How To Cover Pimples, Scars, Cystic Acne, Blackheads & Oil" by Cassandra Bankson. The analytical focus of this paper is on the "before-after" phenomenon, which is a condensed narrative formula of the change of the initial state in some unit of time into another, new and altered state; the change functioning similarly to magical fairy tales "transformations, like the one in Cinderella" (Levy and Rook 381). Besides, the makeover process must be revealed to the interested public because the process of becoming bears higher relevance than the goal or the achievement itself (Jones 15-16). However, the selected video material with its structural features deviates from, for this video genre, the typical position of the productive mechanism of the desired effect and is read as the position of a normative ethical agent. In addition to the observed correlation of the selected material and the thesis on the predominance of the ideal of beauty as an ethical requirement, the analysis of the selected video makeup tutorial points to the need for a more detailed elaboration of the parameters and features of neo/feminist debates on the problem of beauty and its representation.